Návrh kalibračního boxu - Šácha, Tomáš (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2022)
Diplomová práce se zabývá popisem základních fotometrických veličin, světelných zdrojů a jejich parametrů. Taktéž je v práci popsán jasový analyzátor LumiDISP, pro který je kalibrační box navrhován. V další části diplomové práce je řešen návrh kalibračního boxu v programu Inventor a později simulace kalibračního boxu v programu Ansys Speos. Simulace v programu Ansys Speos vedli k určení počtu světelných zdrojů v kalibračním listu, jež pak byli použity pro výrobu. Práce dále popisuje postupy a dílčí části návrhu a výroby kalibračního boxu, včetně jeho oživení a odzkoušení.

The diploma thesis deals with the description of basic photometric quantities, light sources and their parameters. The work also describes the LumiDISP luminance analyzer, for which the calibration box is designed. The next part of the diploma thesis deals with the design of the calibration box in the Inventor program and later the simulation of the calibration box in the Ansys Speos program. The simulations in Ansys Speos led to the determination of the number of light sources in the calibration box, which were then used for production. The work also describes the procedures and partial parts of the design and production of the calibration box, including its revitalization and testing.
Design of the calibration box
Keywords: Kalibrační box; Světelné zdroje; Světlo; Jasový analyzátor; Inventor; Ansys Speos; Eagle Autocad; Calibration box; Light sources; Light; Brightness analyzer; Inventor; Ansys speos; Eagle Autocad